Domestic violence and abuse: an exploration and evaluation of a domestic abuse nurse specialist role in acute health care services - McGarry, Julie (Wiley, 2017)
Aims and objectives: The aim of the present study was to explore the experiences of clinical staff in responding to disclosure of domestic violence and abuse (DVA) and to evaluate the effectiveness of training and support provided by a dedicated Domestic Abuse Nurse Specialist across one acute National Health Service (NHS) Trust in the UK. Background: The impact of DVA is well documented and is far reaching. Health care professionals have a key role to play in the effective identification and management of abuse across a range of settings. However there is a paucity of evidence regarding the constituents of effective support for practitioners within wider non-emergency hospital based services. Design: A qualitative approach semi-structured interviews (n=11) with clinical staff based in one acute care Trust in the UK. Interviews were informed by an interview guide and analysed using the Framework approach. Findings: The organisation of the NS role facilitated a more cohesive approach to management at an organisational level with training and ongoing support identified as key facets of the role by practitioners. Time constraints were apparent in terms of staff training and this raises questions with regard to the status continuing professional development around DVA. Conclusions: DVA continues to exert a significant and detrimental impact on the lives and health of those who encounter abuse. Health care services in the UK and globally are increasingly on the frontline in terms of identification and management of DVA. This is coupled with the growing recognition of the need for adequate support structures to be in place to facilitate practitioners in providing effective care for survivors of DVA. Relevance to clinical practice: This study provides an approach to the expansion of existing models and one which has the potential for further exploration and application in similar settings.